What enables agricultural diversification in the Eastern Gangetic Plains? Learning from past success - Jannat, Arifa; Kishore, Avinash; Jackson, Tamara; Rahman, M. Wakilur; Haque, Md. Mojammel; Rashid, Md. Mamunur; Chowdhury, Tapan; Das, Kalyan Kanti; Joshi, Indu Raj (Wiley, 2025)
The increasing significance of agricultural diversification lies in its ability to improve the productivity, profitability, and sustainability of farming systems. This research investigated how diversification occurs and what enables farmers to shift from one system to another. A thematic analysis was employed for 13 case studies from Bangladesh, India, and Nepal. Our analysis revealed that agricultural diversification was predominantly practiced by marginal and small-scale farmers, and driven by location, growing market demand, and utilization of improved crop varieties. Motivation for diversification included potential increased returns and more consistent income streams. Technical advances (improved crop varieties, seeds, and techniques) and institutional involvement (new market arrangements) have resulted in increased incomes, diverse livelihoods, women's empowerment, and new market opportunities. Through the utilization of case studies, we offer valuable perspectives that can improve the effectiveness of suitable policies and collaborations that can enhance the welfare of farmers and contribute to regional food security.